2021
DOI: 10.1111/cns.13661
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of non‐canonical Wnt signalings does not compromise blood‐brain barrier protection conferred by upregulating endothelial Wnt/β‐catenin signaling following ischemic stroke

Abstract: Background Endothelial canonical (Wnt/β‐catenin) and non‐canonical Wnt signalings (Wnt/PCP and Wnt/Ca2+) promote blood‐brain barrier (BBB) development and antagonize each other. However, the effects of ischemic stroke on endothelial canonical and non‐canonical Wnt signalings are unclear. Further, how non‐canonical Wnt signalings are influenced by upregulation of endothelial Wnt/β‐catenin signaling and subsequently affect BBB function following ischemic stroke have not been studied. Methods First, we determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The canonical Wnt/β-catenin signaling pathway is a key regulator of the BBB and is critical for the stabilization of brain endothelial tight junctions. [39][40][41] Lithium, the first GSK-3β inhibitor, increases the phosphorylation of GSK-3β at Ser9 in vivo and upregulates Wnt/βcatenin signaling. 42 Although a previous study reported the effect of lithium on BBB damage in experimental ICH, the mechanism was not clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The canonical Wnt/β-catenin signaling pathway is a key regulator of the BBB and is critical for the stabilization of brain endothelial tight junctions. [39][40][41] Lithium, the first GSK-3β inhibitor, increases the phosphorylation of GSK-3β at Ser9 in vivo and upregulates Wnt/βcatenin signaling. 42 Although a previous study reported the effect of lithium on BBB damage in experimental ICH, the mechanism was not clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical Wnt/β‐catenin signaling pathway is a key regulator of the BBB and is critical for the stabilization of brain endothelial tight junctions 39–41 . Lithium, the first GSK‐3β inhibitor, increases the phosphorylation of GSK‐3β at Ser9 in vivo and upregulates Wnt/β‐catenin signaling 42 .…”
Section: Discussionmentioning
confidence: 99%
“…66 Interestingly, normalization of non-canonical Wnt signaling does not compromise BBB protection conferred by upregulating endothelial Wnt/β-catenin signaling following ischemic stroke. 67 This suggests that a balance between canonical and noncanonical Wnt signaling pathways may be crucial for maintaining BBB integrity. pathway could significantly influence outcomes following ischemic stroke.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Recent studies further support endothelial cells and associated Wnt/β-catenin signaling involved in barrier maintenance and transporter regulation. 35 BBB breakdown facilitates entry of neurotoxic blood-derived products into the brain, enhancing the neuroinflammatory response 6 and AD pathogenesis. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies further support endothelial cells and associated Wnt/b-catenin signaling involved in barrier maintenance and transporter regulation. [3][4][5] BBB breakdown facilitates entry of neurotoxic blood-derived products into the brain, enhancing the neuroinflammatory response 6 and AD pathogenesis. 7,8 During peripheral chronic inflammation, some circulating inflammatory factors, such as C-reactive protein (CRP), have the potential to act on the blood-facing endothelia in the brain, facilitating or causing AD pathology.…”
Section: Introductionmentioning
confidence: 99%